Non-preference for oviposition and antibiosis in bean cultivars to Bemisia tabaci biotype B (Hemiptera: Aleyrodidae) - Da Silva, Anderson Goncalves; Boica Junior, Arlindo Leal [UNESP]; Farias, Paulo Roberto S.; Rodrigues, Nara Elisa L. [UNESP]; De Souza, Bruno Henrique S. [UNESP]; Bottega, Daline Benites [UNESP]; Chiorato, Alisson Fernando (Soc Colombiana Entomologia-socolen, 2014)
Among the pests that cause reduction on common bean yield, the whitefly Bemisia tabaci biotype B (Hemiptera: Aleyrodidae) stands out. The insect causes direct damages due to its feeding on plants and indirect damages by the sugary excretion of honeydew, providing the development of the sooty mould. In addition this species is an important vector of virus such as the golden bean mosaic virus. Thus, this work aimed to study the non-preference for oviposition and antibiosis in bean cultivars to the whitefly. Experiments were carried out in a greenhouse at Jaboticabal, SP, Brazil, from January to March 2012. The following cultivars were used in the assays: IAC-Centauro, IAC-Una, IAC-Formoso, IAPAR-81, IPR-Eldorado, IPR-Siriri (all resistant); and Perola and IAC-Harmonia (both susceptible), previously screened from field experiments. Cultivars IAC-Harmonia, IPR-Eldorado, IAPAR- 81 and IPR- Siriri were the least preferred for oviposition; and the cultivar IAC-Harmonia extended the whitefly life cycle, expressing nonpreference for feeding and or/antibiosis-type resistance.
Keywords: Whitefly; Phaseolus vulgaris; Genetic resistance; Categories and levels of resistance